Static-priority scheduling of sporadic messages on a wireless channel - Andersson, Björn (2014)
Consider the problem of scheduling sporadic messages with deadlines on a wireless channel. We propose a collision-free medium access control (MAC) protocol which implements static-priority scheduling and present a schedulability analysis technique for the protocol. The MAC protocol allows multiple masters and is fully distributed; it is an adaptation to a wireless channel of the dominance protocol used in the CAN bus. But unlike that protocol, our protocol does not require a node having the ability to receive an incoming bit from the channel while transmitting to the channel.